Immune biology of allogeneic hematopoietic stem cell transplantation models in discovery and translation - Blazar, Bruce R.; Sociâe, Gâerard (Elsevier/AP, 2013)
This book provides clinical and scientific researchers with a deep understanding of the current research and the implications for translational practice. By providing an overview of immune biology of HSCT, an explanation of immune rejection and detail on antigens and their role in HSCT success, this book embraces biologists and clinicians who need a broad view of the deeply complex processes involved. It then moves on to discuss the immunobiology mechanisms that influence graft-versus-host disease (GVHD), graft-versus-leukemia (GVL) effect, and transplantation success. Using illustrative figures, highlighting key issues, describing recent successes and discussing unanswered questions, this book sums up the current state of HSCT to enhance the prospects for the future.